Trucks Under Siege : The Costs of Crime and Insecurity to the Transport Industry in Papua New Guinea - Lakhani, Sadaf (World Bank, Washington, DC, 2014)
The Highlands Highway is a lifeline for the economy of Papua New Guinea. The transport and haulage industry is seriously affected by infrastructure and law and order constraints, but it has also found innovative ways to manage risks. This case study examines two locally owned, medium-sized haulage companies about the challenges they face. Their stories provide a fascinating look into what it takes to run a haulage firm in Papua New Guinea, and the day-to-day risks faced by managers, drivers, and other staff. The challenges include: generally poor road conditions suffering from insufficient investment, poor construction, and corrupt practices; claims for compensation from the many villages and landowner groups located along the Highlands Highway; and a buoyant black market in stolen fuel. The companies utilize a number of risk management techniques, including: constant electronic monitoring; high-tech equipment such as GPS mapping systems and truck modifications; employment of public relations or road liaison officers; high-cost insurance policies; paying the underfunded police to ensure its public service; workplace monitoring systems and procedures; investment in human resources and training; generous salaries for truck drivers; private security escorts; safe commuter transportation for local staff; specific measures to ensure safety of female staff; and reliance on international staff at senior levels. These measures incur increased business costs which are then passed onto consumers. As a result, business expansion is constrained and prospective new suppliers face barriers to market entry.